EFISIENSI BIOREEFTEK SEBAGAI MEDIA PERTUMBUHAN KARANG DI PULAU RUBIAH SABANG - Muhammad Arif Nasution; Munandar Munandar (Universitas Teuku Umar, 2018)
This technology is known as bioreeftek technology. Bioreeftek is a technology developed by the KKP Research and Observation Center (Ministry of Maritime Affairs and Fisheries) in the past few years. This research will examine the number of coral recruitment in coconut shells as natural artificial substrates in 3-5 and 8-10m depths. The coconut shells module composed of 9 pieces consisting of 3 modules installed 1 coconut shell each pole, 3 modules installed 2 coconut shells each pole, and 3 coconut shells attached 3 coconut shells each pole. Retrieval of coral sapling data for about ±4 months. Data is taken directly (in situ) by looking the number of juvenils attached to each substrate. The results obtained show the attachment of two genera of juvenil namely acropora and pocillopora at each depth. The highest number of attachments is found in modules that have 3 shells in each module. The best depth for juvenil attachment is at a depth of 3-5m.